Effect of Environmental Turbulence, Value Creation on Cost Leadership Strategy and Its Impact on Competitive Advantage of Coffee Shop SMEs, Jakarta, 2021 - Virgo Simamora; Indrianti Sulistianingsih (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This explanatory research aims to explain the effect of environmental turbulence and value creation on the cost leadership strategy and its impact on competitive advantage in MSME Coffee Shops in DKI Jakarta. The population of this research is all MSME Coffee Shops in North Jakarta, whose number is unknown. Using a purposive sampling technique, researchers selected 100 MSME Coffee Shops in North Jakarta owned by millennials to participate in this study. Data was collected using a questionnaire distributed online via a google form. The results of this study explain that environmental turbulence affects the cost leadership strategy. Similarly, there is a value creation effect on the cost leadership strategy. In this study, the researcher found that the cost leadership strategy impacted the competitive advantage of coffee shops. This study did not find a direct effect of environmental turbulence on competitive advantage and a direct effect of value creation on competitive advantage. The results of this study indicate that the cost leadership strategy has an important role in creating a competitive advantage for MSME Coffee Shops. Therefore, MSMEs need to consider external and internal issues in strategy formulation.